PENGEMBANGAN MODUL MATEMATIKA BERBASIS PENDEKATAN SAINTIFIK PADA MATERI BANGUN DATAR KELAS IV - Sherly Mellinia; Erfan Ramadhani; Arief Kuswidyanarko (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article explains a study that aims to find out how the validity, feasibility, and benefit of a scientific approach-based Mathematics module for elementary school students at grade IV toward two-dimensional materials. The research method used is research and development. The method used for data collection was a questionnaire. The results of research and development were conducted with several stages by using the 4D development research model. The results of the module validity that were based on the validation of material experts were 93% categorized as very valid, 95% from linguists were categorized as very valid, 92% from media experts were categorized as very valid, and the feasibility based on the assessment of the teacher's responses with a percentage of 93% was categorized as very feasible. Subsequently, the assessment of the module feasibility based on student responses by 10 indicators was obtained 92% categorized as very feasible. Thus, the learning media for the mathematics module based on a scientific approach was very feasible to be used for elementary school students at grade IV.